The Impact Of Service Quality On Customer Satisfaction At Narassi Coffee In Tasikmalaya City: - Fikri, Muhammad; Hidayati, Reny; Jakiyah, Ulpah (CV. Utami, 2025)
Customer satisfaction is a key factor in the success of service-based businesses, including coffee shops. This study aims to examine the impact of service quality on customer satisfaction at Narassi Coffee in Tasikmalaya. Service quality is assessed through five main dimensions: physical evidence, reliability, responsiveness, assurance, and empathy. The research uses a descriptive quantitative approach with purposive sampling. Data were collected through questionnaires distributed to 60 respondents with varying visit frequencies. The results indicate that service quality is closely related to customer satisfaction. The better the service provided, the higher the customer satisfaction. This finding emphasizes that focusing on service quality is crucial for maintaining and enhancing customer satisfaction in the increasingly competitive coffee shop industry.